TRANSFORMASI INFRASTRUKTUR IRIGASI PEDESAAN: IMPLEMENTASI KONSTRUKSI PASANGAN BATU GUNUNG MELALUI PEMBERDAYAAN HIPPA DESA PUTAT LOR, GONDANGLEGI - Heru Setiyo Cahyono; Endrik Soedjarwoko; Annisa’ Carina (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2026)
The deterioration of irrigation infrastructure in Putat Lor Village, Gondanglegi District, poses a significant obstacle to agricultural productivity due to high sedimentation and the collapse of earthen channel banks. This article discusses the transformation of civil engineering research into a community service activity through the implementation of mountain stone (quarry stone) masonry construction based on community empowerment. The implementation method employed a Participatory Action Research (PAR) approach, involving the Water User Farmers Association (HIPPA) from planning and technical training to self-managed construction. The results indicate that the utilization of local Gondanglegi mountain stone offers mechanical advantages in the form of strong interlocking bonds and a cost efficiency of 21% compared to river stone materials from outside the region. Physically, a 100-meter sturdy tertiary irrigation channel has been constructed. Socially, there was an increase in the partners' capacity regarding standard mortar mixing techniques (1:4) and drainage maintenance management. This program recommends the use of local materials and active ommunity involvement as a sustainable model for rural infrastructure revitalization.